2008
DOI: 10.1128/mcb.02217-07
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Coactivator SAYP Is a Trithorax Group Signature Subunit of the PBAP Chromatin Remodeling Complex

Abstract: SWI/SNF ATP-dependent chromatin remodeling complexes (remodelers) perform critical functions in eukaryotic gene expression control. BAP and PBAP are the fly representatives of the two evolutionarily conserved major subclasses of SWI/SNF remodelers. Both complexes share seven core subunits, including the Brahma ATPase, but differ in a few signature subunits; POLYBROMO and BAP170 specify PBAP, whereas OSA defines BAP. Here, we show that the transcriptional coactivator and PHD finger protein SAYP is a novel PBAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 41 publications
9
95
0
1
Order By: Relevance
“…1C Lower) indicated that SAYP was associated only with the PBAP subfamily of the Brahma complex (3). This is in agreement with the results reported by (14).…”
Section: Sayp Is Present In the High-molecular-weight Complex Containingsupporting
confidence: 94%
See 3 more Smart Citations
“…1C Lower) indicated that SAYP was associated only with the PBAP subfamily of the Brahma complex (3). This is in agreement with the results reported by (14).…”
Section: Sayp Is Present In the High-molecular-weight Complex Containingsupporting
confidence: 94%
“…3B) and found that these patterns overlap considerably. Together with the data by (14), this fact demonstrates that SAYP shares its chromosomal sites with both TFIID and Brahma.…”
Section: Sayp Interacts With Tfiid and Brahma Components In Drosophilasupporting
confidence: 69%
See 2 more Smart Citations
“…While the manuscript was in preparation, Chalkley et al (14) reported that the PBAP complex contains a third specific subunit, Supporter of activation of Yellow protein (SAYP), that is required for the stability of Bap180 and Bap170. Although homologues of this subunit have not been reported in purified vertebrate PBAF complexes, genome-wide gene expression changes in S2 cells after RNAi knockdown of SAYP, Bap170, and Bap180 were strongly correlated, suggesting that the three proteins act as a functional unit.…”
Section: Discussionmentioning
confidence: 99%